Analisis Sumber Daya Perusahaan Dan Lingkungan Eksternal: Studi Kasus pada Industri Kreatif Digital Pasca Pandemik Covid 19 - Ermaya, Sir Kalifatullah; Mulyana, Iwan; Nur Laela Ermaya, Husnah; ARR, Tryiis (Coopetition : Jurnal Ilmiah Manajemen, 2024)
This research highlights company resource variables and the external environment in the digital creative industry in West Java, which is registered with Aspiluki. There were 25 respondents in this study, consisting of owners and managers. This research uses quantitative and descriptive research methodologies. Company resources are everything that the company owns and can control. Meanwhile, the external environment is the environment outside the organization that can influence a company. The results show that the biggest indicator of the company resource variable is "the accuracy of using computer-based systems to analyze customer and market information." Meanwhile, the biggest indicator of external environmental variables is "the power of suppliers in determining costs to the company." The lowest indicator for the company resource variable is "developing and maintaining computer-based communication relationships with customers." Therefore, researchers suggest that companies should improve service quality by offering customer service 24 hours a day instead of normal office hours, which usually only involve 5 working days a week. Meanwhile, the lowest indicator for external environmental variables is "changes in government policies that affect digital creative businesses." Therefore, researchers suggest that the government provide policies that can provide more contributions to companies in the digital creative industries.